2022
DOI: 10.3389/fnut.2022.888360
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Extracts From Sea Cucumbers and Tunicates Induce a Pro-osteogenic Effect in Zebrafish Larvae

Abstract: Bone metabolic disorders such as osteoporosis are characterized by the loss of mineral from the bone tissue leading to its structural weakening and increased susceptibility to fractures. A growing body of evidence suggests that inflammation and oxidative stress play an important role in the pathophysiological processes involved in the rise of these conditions. As the currently available therapeutic strategies are often characterized by toxic effects associated with their long-term use, natural antioxidants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Likewise, the ethyl acetate fraction of H. scabra extracts, rich in phenolic compounds, inhibited pro-inflammatory cytokine synthesis at both the transcriptional and translational levels, mainly inducible nitric oxide synthase (iNOS), nitric oxide (NO), interleukin-1β (IL-1β), prostaglandin E 2 (PGE 2 ), and tumor necrosis factor-α (TNF-α) [ 37 ]. Carletti et al [ 35 ] demonstrated that polyphenol-rich sea cucumber ( H. forskali , H. arguinensis , and H. mammata ) extracts, mainly hydroethanolic extracts, exhibited anti-inflammatory activity via COX-2 inhibition and osteogenic activity in a zebrafish ( Danio rerio ) model. However, phenolic-rich Holothuria atra extracts were used to determine the antioxidant efficacy against 7,12-dimethylbenz[a]anthracene (DMBA)-induced hepatorenal dysfunction [ 31 ].…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…Likewise, the ethyl acetate fraction of H. scabra extracts, rich in phenolic compounds, inhibited pro-inflammatory cytokine synthesis at both the transcriptional and translational levels, mainly inducible nitric oxide synthase (iNOS), nitric oxide (NO), interleukin-1β (IL-1β), prostaglandin E 2 (PGE 2 ), and tumor necrosis factor-α (TNF-α) [ 37 ]. Carletti et al [ 35 ] demonstrated that polyphenol-rich sea cucumber ( H. forskali , H. arguinensis , and H. mammata ) extracts, mainly hydroethanolic extracts, exhibited anti-inflammatory activity via COX-2 inhibition and osteogenic activity in a zebrafish ( Danio rerio ) model. However, phenolic-rich Holothuria atra extracts were used to determine the antioxidant efficacy against 7,12-dimethylbenz[a]anthracene (DMBA)-induced hepatorenal dysfunction [ 31 ].…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…The total antioxidant capacity was obtained by FRAP (Ferric Reducing Antioxidant Power) method described by Moure et al ( 63 ). The method reported by Carletti et al ( 64 ) was slightly modified for the measurement of FRAP of the egg white-based beverage samples.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 370 sea cucumber were used for toxic metal analyses, H. arguinensis (n = 123), H. forskali (n = 124) and H. mammata (n = 123). The phylogenetic identi cation was made in accordance to the methodology described by Carletti et al (2022). The animals were classi ed for each season and species, and after sorted by sex (male and female).…”
Section: Raw Materials and Sample Preparationmentioning
confidence: 99%